Pulsed gas aggregation for improved nanocluster growth and flux. Issue 5 (25th February 2014) - Drache, Steffen; Stranak, Vitezslav; Berg, Florian; Hubicka, Zdenek; Tichy, Milan; Helm, Christiane A.; Hippler, Rainer
<x xml:space="preserve">Abstract</x> Growth of Cu nanoparticles in a pulsed gas aggregation cluster source was studied. The cluster growth is enhanced by an energy transport inside the aggregation chamber fed by argon that is delivered in short pulses repeated with low frequency. The effect of pressure, varied during the pulse, on the cluster growth was estimated from time‐resolved measurements of mass/size cluster distribution. The cluster mass and the cluster production well correlate with pressure changes. Several stages of cluster growth during the gas‐pulse were recognized. Not only larger clusters but also significantly enhanced particle and mass fluxes were observed.